Half‐sandwich Ruthenium (II) complexes with triphenylamine modified dipyridine skeleton and application in biology/luminescence imaging. (27th August 2019) - Ge, Xingxing; Liu, Xicheng; Tian, Zhenzhen; Chen, Shujiao; Liu, Xinyu; Guo, Lihua; Gong, Peiwei; Ling, Baoping; Yuan, Xiang‐Ai; Liu, Zhe
Abstract : Four half‐sandwich ruthenium II (Ru II ) complexes with triphenylamine‐modifed dipyridine frameworks were synthesized and characterized. The cytotoxicity of target complexes toward A549 (lung cancer cells), HeLa (cervical cancer cells) and HepG2 (hepatoma cells) were obtained by the MTT assay, which were superior to cisplatin with the IC50 values changed from 2.4 ± 0.1  μ M to 9.2 ± 2.7  μ M. Meanwhile, complexes possess the ability of antimetastasis to cancer cells. Ru II complexes could be transported by serum albumin, catalyze the conversion of NADH (the reduced state of nicotinamide‐adenine dinucleotide) to NAD + and induce the accumulation of reactive oxygen species, which confirmed the antineoplastic mechanism of oxidation. Ru II complexes could enter A549 cells followed by a non‐energy dependent cellular uptake mechanism, target lysosomes with the Pearson's colocalization coefficient of 0.75, lead to lysosomal damage, disturb the cell cycle (S phase), and eventually induce apoptosis. The results demonstrate that these Ru II complexes are potential anticancer agents with dual functions, including metastasis inhibition and lysosomal damage. Abstract : Half‐sandwich Ruthenium (II) complexes show potential anticancer activities, enter A549 cells followed by a non‐energy dependent mechanism, change the mitochondrial membrane potential and increase the ROS level, cause the accumulation in lysosome and lead to lysosomal injury, and eventually induce apoptosis.